Cardiotocography in early labour: a screening test for predicting fetal outcome - Anandabaskar, Vinothini; B., Hiremath P.; B., Sanjeevkumar; Arthi, Nivedhana; R., Rathnapratheep (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Fetal surveillance during labour is important to ensure delivery of a healthy baby with minimum intervention. Various parameters can be used to assess the fetal wellbeing like fetal movements perceived by the mother and monitoring of fetal heart rate. The objective of this study is to evaluate the efficacy of cardiotocography in early labour in predicting fetal outcome. Methods: A prospective hospital based cross sectional study was conducted on a total of 160 antenatal women in early labour with gestational age ≥ 37 weeks of gestation. Cardiotocogram was recorded for 20 minutes with the antenatal women in left lateral position. They are followed up till delivery and the mode of delivery of the baby was recorded. After delivery of the baby, the presence of fetal distress was assessed by careful examination of the neonate and colour of liquor. Results: Among the antenatal women, cardiotocography findings were normal in 74.4%, suspicious in 15% and pathological in 10.6%. The sensitivity of CTG in evaluating fetal outcome was found to be 84.6%, and the specificity was found to be 85.8%. The positive predictive value was 53.7% and the negative predictive value was 96.6%. Conclusions: Hence from the above study, it is can be concluded that the false positive rate of CTG is higher. Hence CTG cannot be used a sole indicator of fetal hypoxia. But in a resource limited setting, CTG is definitely a good screening test to predict the fetal outcome.